GRACEFUL LABEING AND RHO TOPI LABELING ON THE 8-BINTANG GRAPH WITH C3 FOR N ODD - Amri, Zulfi; Harahap, Tua Halomoan; Irvan, Irvan (ZERO: Jurnal Sains, Matematika dan Terapan, 2018)
This paper we propose graceful labeling and  labeling on a graph then referred to as 8-Bintang graph, the basic idea of formulation graceful labeling and  labeling on an alfabet bintang graphs wih the question a stars graph . Then we constructing graceful labeling and  labeling on the 8-Bintang graph with circle graph  for  odd.  The results obtained are illustrated in the theorem that the 8-Bintang graph with  for  odd has the following graceful labeling with the proof.